Back to the Drawing Board: Designing Corporate Boards for a Complex WorldBack to the Drawing Board: Designing Corporate Boards for a Complex World, by Carter Colin and Lorsch Jay. Boston: Harvard Business School Press, 2004. - Smallman, Clive (Academy of Management Review, 2005)
The article reviews the book ?Back to the Drawing Board: Designing Corporate Boards for a Complex World,? by Colin Carter and Jay Lorsch.